A two-sided market platform analysis for the electric vehicle adoption: Firm strategies and policy design. (July 2018) - Jang, Dae-Chul; Kim, Bosung; Lee, Su-Yol
Highlights: Platform competition model between electric and gasoline vehicles. Interaction among consumer, energy suppliers, and vehicle manufacturers. Energy costs of vehicles have significant impact on platform competition. The drop in oil prices might not negatively influence electric vehicle sales. EV diffusion policy effectiveness depends on energy costs and target sales level. Abstract: This study explores how to facilitate the electric vehicle (EV) diffusion from a two-sided market platform competition. We develop a stylized model depicting the platform competition between electric and gasoline vehicles by combining indirect network effects of consumer and energy supplier sides as well as vehicle manufacturers' profits. The findings of this study provide several meaningful strategic and policy implications for EV manufacturers and policymakers who wish to enhance EV diffusion. First, EV sales are significantly influenced by indirect network effects from the energy supplier side to the consumer side, and vice versa. This implies that EV manufacturers who wish to boost EV diffusion should implement a strategy providing energy suppliers with incentives to willingly join the EV platform. Second, the dynamic nature of the effects of energy costs on platform competition might render counter-intuitive evidence that the drop in oil prices does not always negatively influence EV sales. This requires EV manufacturers to prepare a contingent strategy adjusting to such unexpected conditions. Third, governments should consider the energy supplier side as well as the consumer side in designing EV diffusion policies. When governments have a very challenging EV diffusion target, a balanced policy, which treats both gasoline and electric vehicle technologies fairly, may be more effective than a consumer subsidy policy.